THE EVOLUTION OF MOZART’S VOCAL STYLE: AN ANALYSIS BASED ON CHURCH MUSIC - Liting, Guo (Scientific Journal of Polonia University, 2024)
This article examines the stylistic influences shaping Mozart’s sacred music, offering an in-depth analysis of its evolution. It identifies two distinct styles: the Salzburgian and contemporary approaches. The Salzburgian style is defined by brevity, counterpoint, and tonal unity, adhering to traditional liturgical requirements. Meanwhile, the contemporary style reflects the influence of secular music, with larger structures, concertante melodies, and thematic contrasts drawn from symphonic and operatic works. A comparison between Mozart’s two Lauretian litanies, Litaniae Lauretanae KV 109 and KV 195, illustrates his compositional development. The earlier litany demonstrates simplicity and compactness, while the later piece shows increased complexity, operatic influence, and a more intricate orchestral role. The analysis highlights how Mozart blended sacred music’s formal rigor with expressive elements from operatic and instrumental traditions, creating a distinctive style that paved the way for future innovations in liturgical music. By drawing from contrapuntal traditions and integrating operatic expressiveness, Mozart’s sacred works reflect his genius in synthesizing diverse influences into a cohesive and innovative musical language.